Sound and recording an introduction - Rumsey, Francis (Focal Press, 2006)
This best-selling book introduces you to the principles of sound, perception, audio technology and systems. Whilst offering vital reading for audio students and trainee engineers, this guide is ideal for anyone concerned with audio, sound and recording - beginners and professionals alike. Comprehensive and easy to understand, this fifth edition is bang up to date, with expanded information on digital audio principles, systems and applications, as well as an extensively updated chapter on MIDI and synthetic audio control.
Includes bibliographical references and index. - Print version record
Keywords: Sound -- Recording and reproducing; Son; Enregistrement et reproduction; TECHNOLOGY & ENGINEERING; Electrical; Sound; Recording and reproducing